(untitled) (Northern International Medical College Journal, 2015)
We are reporting a case of a 10 year old boy admitted in Dhaka Shishu (Children) hospital with the complaints of swelling of both side of inguinal region for 2 months, tenderness of the same area for 1 month and low grade fever for 2 months. With the history and physical examination of the patients our differential diagnosis was Tuberculosis/Lymphoma/Cat scratch disease (CSD). He had only a history of contact with a kitten for 1 week 3 months back but no history of cat scratch or bite. Lymph node biopsy revealed that it was a case of Cat scratch disease. Northern International Medical College Journal Vol.5(1) 2013: 316-317